ANALISIS LINK AND MATCH PADA KURIKULUM 2013 SMK PROGRAM KEAHLIAN TATA BUSANA DITINJAU DARI LULUSAN SMK UNTUK MELANJUTKAN STUDI DAN BERWIRAUSAHA DI KOTA MAKASSAR - Kasriani; Syamsidah; Muhammad Rais (UNM Journal of Technology and Vocational, 2022)
This study aims to find out the description of link and match analysis in the 2013 curriculum of the Vocational School of Fashion Design, to describe the supporting factors for Vocational High School graduates to continue their studies and entrepreneurship and to describe the inhibiting factors for Vocational High School graduates to continue their studies and entrepreneurship. This type of research is qualitative research. Data obtained from interviews and observations with several expert informants. The data analysis technique used a qualitative descriptive analysis technique (componental analysis). Based on the results of research and data analysis, it can be concluded that 1) the description of link and match in the 2013 curriculum of the Vocational High School fashionskills program at SMK Negeri 6 and SMK Negeri 8 Makassar found that schools have not involved the Business World/Industrial World (DU/DI) in determining the curriculum formulation that will be applied in the Competence of Fashion Design Skills, only refers to the national curriculum which is still less relevant to the needs of DU/DI, 2) Supporting factors for link and match analysis in the 2013 curriculum of Vocational High School fashion skills program in terms of SMK graduates to continue their studies and entrepreneurship are internal factors, namely interested factors and external factors, namely the school environment which includes aspects of facilities and infrastructure, competence of educators, and data on SMK graduates who have successfully obtained jobs in the fashion sector, 3) Factors inhibiting link analysis and match in the 2013 curriculum of the Vocational High School, thefashion skills program is reviewed and ri SMK graduates to continue their studies and entrepreneurship are internal factors, namely motivational factors and external factors, namely the family environment which includes economic aspects that affect the capital to work independently and the lack of interest of SMK graduates in the Department of Fashion.